MisterGod, This is Anna : A True Story - Fynn (New York Holt, Rinehart and Winston, 1974)
Tells the story of a young London man who took in a four-year-old orphan named Anna whose pure joy and understanding of God changed his life
card
Keywords: Anna; Christian Biography -- England